The Global Trend of Blended Learning to Support Digitalization of Education: A Bibliometric Analysis - Arifin, Ahmad Zaenal; Widiastuti, Anik; Sudrajat, Sudrajat (Media Komunikasi FPIPS, 2025)
This study discusses blended learning as a new learning method offers learning that applies technology that erases distance and place. We took articles published in scopus journals. Bibliometric analysis was used with the help of Biblioshiny and VOSviewer to analyze numbers, countries, institutions, authors, journals, references, and keywords. In the process of the prism diagram, we found 181 out of a total of 199 initial articles that we analyzed in scopus. in the analysis of the country Indonesia became the most productive country, then the university of cape coast organization became the most active institution, the international journal emerging of technologies became the most published journal, while Barvell became the researcher who published the most research, the most relevant Keywords are students, learning and education. Blended learning will continue to grow with the challenges of technology-based learning methods. The implications of this research show that the global trend of blended learning can continue to be developed.